The Role of Islamic Education in Reducing Socio-Economic Inequality in Society - Nur Rahma Binti Amran (Demagogi: Journal of Social Sciences, Economics and Education, 2025)
Social and economic inequality is a significant global challenge, including in Indonesia, encompassing the economy, education, health, and employment opportunities. The dominant capitalist economic system often exacerbates inequality, benefiting the already prosperous and harming the less fortunate.The policy of eradicating socio-economic inequality through education includes individual freedom to develop their abilities, equal access to education and protection for women in rural areas, and active participation of local governments in social equality. Sharia-based economic education is a concrete solution that teaches the principles of a just and sustainable economy, and instills important moral values.With the right collaboration between education and policy, it is hoped that social and economic inequality can be significantly reduced, creating a more just and prosperous society.